Ankle Sprain Versus Muscle Strain Injury in Professional Men's Basketball: A 9-Year Prospective Follow-up Study. Issue 6 (11th June 2019) - Rodas, Gil; Bove, Toni; Caparrós, Toni; Langohr, Klaus; Medina, Daniel; Hamilton, Bruce; Sugimoto, Dai; Casals, Martí
Background: Ankle sprain is the most common injury in basketball players. However, in our routine clinical evaluation, we observe a high frequency of muscle injury. Currently, no reliable information is available regarding the magnitude of these types of injury. Purpose: To describe the type and rate of muscle injuries in male basketball players and discuss clinical management and prevention strategies. Study Design: Descriptive epidemiology study. Methods: A total of 59 professional male basketball players were evaluated over 9 seasons (2007-2015). All injuries during the study period were registered through use of a validated electronic medical record system. Results: We analyzed 463 injuries, of which 207 resulted in time loss and 256 required medical attention, for a total exposure time of 42, 678 hours for the 59 players involved in the study. Muscle strains and ankle sprains accounted for 21.2% (n = 98) and 11.9% (n = 55) of all injuries, respectively. The global incidence rate was 10.8 injuries per 1000 player-hours (95% CI, 9.9-11.9). The global injury burden was 53.9 days lost due to injuries per 1000 hours for a total exposure time. The incidence rate of muscle strains (2.3; 95% CI, 1.9-2.8) was higher than that of ankle sprains (1.3; 95% CI, 1-1.7). The incidence rate for muscle injuries for the entire study period was 1.8 times higher (95% CI, 1.28-2.49) than that for ankle sprains. Conclusion: In this study, muscle injuries were more commonly observed compared with ankle sprains. Prevention strategies for muscle injuries may be worth discussing.